Lectio et Disputatio en el prólogo del Contra legem Sarracenorum de Riccoldo da Monte di Croce - Cándida Ferrero Hernández (Mélanges de la Casa de Velázquez, 2019)
In medieval times, the writing of exegetical texts constitutes a common practice to the three religions of the Book, with different facets and modalities that will depend on the perspective of the author. The case presented in this counterpoint, the analysis of the prologue of the Contra legem Sarracenorum of the Dominican Riccoldo da Monte di Croce (ca. 1300), offers a double peculiarity: on the one hand the apologetic textual value, which is observed through the use of the psalm CXVIII; on the other, the use of this psalm which pushes the author to his controversial discourse against Islam. Thus, although the author uses his knowledge of Islamic texts in the course of his treaty, omitting Christian texts, in the first instance he seeks to strengthen his disputatio through lectio, which goes beyond mere exegetical comment.